Digital Literacy Analysis to Support Digital Transformation in an Effort to Increase User Interest in The Sibakul Application in Cooperatives Assisted by The Yogyakarta Cooperatives and SMEs Office - Muhammad Whisnu Ade Mulia (PT SOLUSI EDUKASI BERDIKARI, 2024)
The rapid development of technological systems encourages DISKOP UKM DIY to undergo digital transformation from conventional to more modern. This digital transformation is the key to success for cooperatives and businesses to survive, rise and thrive in the digital era, especially where the business and market environment is rapidly changing. The quantitative approach model used in the research will be discussed below this chapter. The purpose of this model is to study how digital transformation impacts the cooperatives assisted by the DIY Cooperative and SME Agency. Of the assessment indicators, the aspect of problems related to digital technology was the point that received the lowest response among others. The DIY Department of Cooperatives and SMEs needs to increase the intensity and number of participants in educational and socialization activities through the Sibakul Jogja digital application to understand the importance of digital transformation.